The coagulation profile as a marker for acute appendicitis in the paediatric population: Retrospective study - Anna Morandi; Elisa Cipriani; Filippo Parolini; Dario Consonni; Edoardo Calderini; Stefania Franzini; Ernesto Leva (Wolters Kluwer Medknow Publications, 2020)
Introduction: Appendicitis is the commonest and most frequently misdiagnosed acute abdominal surgical illness in the paediatric population worldwide. The aim of this study is to evaluate the role of coagulation profile in acute appendicitis (AA) in children. Materials and Methods: we retrospectively collected data of patients submitted to appendectomy from 2011 to 2017. According to histopathology, patients were divided into three groups: not histologically confirmed AA (NAA), simple AA (SAA) and complicated AA (CAA). White blood cell (WBC) count, relative neutrophilia (Neutr%), C-reactive protein (CRP), prothrombin time ratio (PTratio), activated partial thromboplastin time ratio (APTTratio) and fibrinogen (Fib) were compared among groups. Results: Three hundred and seven patients were included: 57 NAA, 184 SAA and 66 CAA. WBC was significantly different among groups: CAA (mean 16.67 × 103/ml), SAA (14.73 × 103/ml, P= 0.01) and NAA (10.85 × 103/ml, P< 0.0001). Significant differences were found for Neutr% (mean CAA 81.14 vs. SAA 77.03 P= 0.006, vs. NAA 63.86 P< 0.0001) and CRP (mean NAA 2.56, SAA 3.26, CAA 11.58, P< 0.0001). PTratio and Fib increased with the severity of AA receiver operator characteristic curves were similar for CRP (0.739), Fib (0.726), WBC (0.746) and Neutr% (0.754), while for PTratio and aPTTratio were 0.634 and 0.441, respectively. Conclusions: extrinsic coagulation pathway is altered in AA, especially in CAA. Coagulation can be useful in the diagnostic and perioperative anaesthetic management of AA in children. Fib seems to have the highest accuracy.